The effects of perceived leadership styles and organizational citizenship behavior on employee engagement: the mediating role of conflict management - Mohd Soieb, Ahmad Zairy; Othman, Jamilah; D' Silva, Jeffrey Lawrence (Canadian Center of Science and Education, 2013)
In recent years, employee engagement has become a topic that keeps coming up and often debated by the top management particularly in the public sector agencies due to the differences in the work and leadership styles, commitment and job performances exhibited by the new officers that seem to generate mix perceptions and, to some extent, disrupt the good relationship between them and senior officers thus destabilizing the organizations. Although this scenario is particularly known to occur in the public sector, adequate research on employee engagement that is heavily influenced by the styles of leadership and organizational citizenship behavior are poorly executed. Meanwhile, conflict management which is believed to mediate the relationship is also misunderstood based on the resulting gap in Social Exchange Theory and Path Goal Theory. This review is part of a growing body of research on employee engagement and it is believed that it will contribute vastly to future research on similar topics.